SUSTAINABILITY IN VERTICAL RESIDENTIAL CONDOMINIUMS: A STUDY IN THE METROPOLITAN REGION OF CAMPINAS (Gestão & Regionalidade, 2023)
Sustainability is a concept that involves three dimensions: environmental, economic and social. In this sense, sustainability should be a concern of vertical residential condominiums, since the large number of urban buildings can negatively impact the environment and people's quality of life. In order to contribute to this theme this work was created. Thus, the work aims to verify and characterize, under the environmental, economic and social dimensions of sustainability, the occurrence of sustainable practices in vertical residential condominiums within the limits of the Metropolitan Region of Campinas. The research method adopted was exploratory research, of a qualitative and quantitative approach, whose data collection was carried out from a field research. In general, the results obtained suggest that the residential condominiums analyzed place a greater emphasis on the economic dimension and less on the social and environmental dimensions.
Keywords: Sustainability. Vertical Residential Condominiums. Sustainable Practices